Hands-free smartphone-based diagnostics for simultaneous detection of Zika, Chikungunya, and Dengue at point-of-care. - Ganguli, A.; Ornob, A.; Yu, H.; Damhorst, G.; Chen, W.; Sun, F.; Bhuiya, A.; Cunningham, B.; Bashir, R. (Biomedical Microdevices, 2017)
Infectious diseases remain the world's top contributors to death and disability, and, with recent outbreaks of Zika virus infections there has been an urgency for simple, sensitive and easily translatable point-of-care tests. Here we demonstrate a novel point-of-care platform to diagnose infectious diseases from whole blood samples. A microfluidic platform performs minimal sample processing in a user-friendly diagnostics card followed by real-time reverse-transcription loop-mediated isothermal amplification (RT-LAMP) on the same card with pre-dried primers specific to viral targets. Our point-of-care platform uses a commercial smartphone to acquire real-time images of the amplification reaction and displays a visual read-out of the assay. We apply this system to detect closely related Zika, Dengue (types 1 and 3) and Chikungunya virus infections from whole blood on the same pre-printed chip with high specificity and clinically relevant sensitivity. Limit of detection of 1.56e5 PFU/mL of Zika virus from whole blood was achieved through our platform. With the ability to quantitate the target nucleic acid, this platform can also perform point-of-care patient surveillance for pathogen load or select biomarkers in whole blood.